Anti-malarial plants in Ethiopia and their activities on drug-resistant malaria. (12th January 2022) - Sema, Yimeslal Atnafu; Waktola, Teshale Areda
Abstract: In Ethiopia, the impacts of malaria continue to cause a many number of morbidity and mortality that accounts to most-outpatient observations. Ethiopia recently designed to attain nationwide malaria control by 2030 by beginning sub-national elimination in districts with low malaria transmission. However, the rise of drug-resistant parasites, especially Plasmodium falciparum hinder the malaria-containment strategies. Plasmodium falciparum and Plasmodium vivax are dispersed all over Ethiopia, and account for 60% and 40% of malaria cases, respectively. The aim of this report was to overview the phytochemical constituents, diversity, and effect of some compound extracts on drug-resistant plasmodium species. Many plant species, a total 200 identified by 82 studies, are used in traditional malaria treatments throughout the country. Allium sativum, Croton macrostachyus, and Carica papaya were the more frequently used medicinal plant species. There are so many phytochemical constituents found in medicinal plants used to treat malaria. Alkaloids, flavonoids, phenolics, terpenoids, and glycosides are the most-reported for their effective activity on drug-resistant malaria.